A conceptual life cycle-based sustainability framework for assessing transportation vehicles. Issue 4 (2018) - Mitropoulos, Lambros K.; Prevedouros, Panos D.
Life cycle assessment has been used extensively in the transportation sector to determine impacts of transportation infrastructure and other components; however, the majority of these studies focus on environmental life cycle impacts. This study presents applications of the life cycle assessment method in transportation and develops a sustainability framework that incorporates life cycle impacts for assessing urban transportation vehicles. The framework uses five sustainability dimensions, a set of 32 sustainability indicators, 14 midpoint impacts, seven endpoint impacts and three sustainability indices for the assessment of different technologies of urban transportation vehicles. The framework aims to enhance decision making by aggregating data, which are used to quantify multiple indicators, into a different form of indices representing environment, technology performance, energy, economy and user-based impacts.